2018
DOI: 10.3329/ajmbr.v4i3.38471
|View full text |Cite
|
Sign up to set email alerts
|

Bio-economic analysis of ESBN fishery of Kumira, the coastal area of Chittagong, Bangladesh

Abstract: The present investigation was conducted from May to December 2005 at Kumira, the representative area of Chittagong coast for bio-socioeconomic analysis of ESBN fishery. In catch composition of Kumira, it was observed that finfish occupied 77.03 %, shrimp 19.82 % and crab 3.15 % and the average catch per boat per day were found 16.6 kg in Kumira. The highest total catch per boat per day (50 kg) was found in October at Kumira. The lowest catch was found (2 kg) in August at Kumira. The average total catch per lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The cultured fishes were Rui, Catla, Pangus, Tilapia, Koi, Sarputi, common carp, Mrigal and Magur in Jamalpur and Sherpur district. Faruk et al (2008) observed that the farmer interviewed were male with an average age of 37 years and the average family size 6; another few study in different place of Bangladesh showed the similar results (Islam et al, 2014;Asif et al, 2015;Hossain et al, 2015;Islam et al, 2015;Sharif et al, 2015;Sultana et al, 2015;Ali et al, 2016;Hossain et al, 2016;Vaumik et al, 2017;Razeim et al, 2017;Zaman et al, 2017;Islam et al, 2017;Habib, 2017 Adhikary et al, 2018a;Mondal et al, 2018a;Mondal et al, 2018b;Adhikary et al, 2018b). But in this study, the interviewed age 34 years old and their average.…”
Section: Discussionmentioning
confidence: 56%
“…The cultured fishes were Rui, Catla, Pangus, Tilapia, Koi, Sarputi, common carp, Mrigal and Magur in Jamalpur and Sherpur district. Faruk et al (2008) observed that the farmer interviewed were male with an average age of 37 years and the average family size 6; another few study in different place of Bangladesh showed the similar results (Islam et al, 2014;Asif et al, 2015;Hossain et al, 2015;Islam et al, 2015;Sharif et al, 2015;Sultana et al, 2015;Ali et al, 2016;Hossain et al, 2016;Vaumik et al, 2017;Razeim et al, 2017;Zaman et al, 2017;Islam et al, 2017;Habib, 2017 Adhikary et al, 2018a;Mondal et al, 2018a;Mondal et al, 2018b;Adhikary et al, 2018b). But in this study, the interviewed age 34 years old and their average.…”
Section: Discussionmentioning
confidence: 56%
“…The noteworthy educational institutions are Shyamnagar Mohsin College (1972), Nurnagar Ashalata High School (1955), Bhurulia Nagbati Secondary School (1945), Patakhali Secondary School (1954), Patakhali Senior Madrasa (1945), Jainagar Hamidia Senior Madrasa (1963 (BBS, 2011). These findings are also supported by some previous study from around the Bangladesh by Islam et al (2014) in Jashore district ; Asif et al (2015) in Jashore district ; Hossain et al (2015) in Dinajpur district ; in Satkhira district ; Rahaman et al (2015) in Jashore district ; Sharif et al (2015) in Jashore district; in Patuakhali district ; Sultana et al (2015) Patuakhali district; Jashore district ; Vaumik et al (2017) in Lalmonirhat district; Razeim et al (2017) in Mymensingh district; Hossain et al (2017) in Brahmanbaria district; Islam et al (2017) in Meherpur district; Asif and Habib (2017) in Jashore district; Adhikary et al (2018a) in Noakhali district; Mondal et al (2018a) in Chittagong coastal area; Mondal et al (2018b) in Chittagong coastal area; Adhikary et al (2018b) in Jashore district. Although the expansion of education sector seems to be slow during last 10 years; but above mentioned educational institutions, recently established some Private Schools, NGO operated Non-Formal Primary School and kindergartens are playing an important role for the promotion of education as well as the socio-economic development of Shyamnagar Upazila.…”
Section: Figure 1 Industrial Chart Of the Shyamnagar Upazilamentioning
confidence: 99%
“…Therefore, present per capita agricultural land of 0.056 ha will decrease to 0.025 ha by 2050 (Islam, 2006). Coastal area, which is one third of the territory of Bangladesh, have gone through major changes over the last half century largely due to frequent and diverse natural disasters with direct and indirect impacts on land resources and its various uses Mondal et al, 2018a;Mondal et al, 2018b). Land is being degraded and lost due to the effects of increased salinity intrusion, inundation of low-lying marshy land, floods and land erosion by the unplanned and haphazard land use of people (Ahmed, 2011;Grases et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baor fisheries resources either entirely or partially supported the livelihood of baor fishers (Islam et al, 2018;Jamil et al, 2022). An accurate assessment of the current situation, the chances and hazards of future changes, and the potential for reducing adverse effects on the quality of human existence are all dependent on regional socioeconomic analysis (Bodrud-Doza et al, 2020;Mondal et al, 2018b;Rahaman et al, 2020;Rashed et al, 2017;Salam et al, 2020;Uddin et al, 2022). With its abundant biological and water resources, the baor area in the Jashore district contributes significantly to the nation's economy (Azad et al, 2020;Jamil et al, 2022).…”
Section: Introductionmentioning
confidence: 99%